Uganda : Technical Assistance Report-Report on the Sectoral Financial Accounts Mission. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses the technical advice and recommendations given by the IMF mission to the authorities of Uganda regarding sectoral financial accounts. The IMF mission reviewed the sectoral financial stocks and transactions data for 2014 and noted that commendable progress has been made in compilation of annual financial accounts. The mission provided suggestions for public release of annual data for the years 2013, 2014, and 2015 by September 30, 2016. The progress on quarterly financial accounts compilation has been slow because source data were not available for some sectors and because of capacity constraints. The IMF mission recommends compilation of these data for internal purposes for sectors and instruments with data availability.